Fuzzy Optimal Control Problem of Several Variables - Altyeb Mohammed Mustafa; Zengtai Gong; Mawia Osman (Advances in Mathematical Physics)
The purpose of this paper is to establish the necessary conditions for a fuzzy optimal control problem of several variables. Also, we define fuzzy optimal control problems involving isoperimetric constraints and higher order differential equations. Then, we convert these problems to fuzzy optimal control problems of several variables in order to solve these problems using the same solution method. The main results of this paper are illustrated throughout three examples, more specifically, a discussion on the strong solutions (fuzzy solutions) of our problems.